Stagnation-point flow of the Walters' B' fluid with slip - F. Labropulu; I. Husain; M. Chinichian (International Journal of Mathematics and Mathematical Sciences)
The steady two-dimensional stagnation point flow of a non-Newtonian Walters' B' fluid with slip is studied. The fluid impinges on the wall either orthogonally or obliquely. A finite difference technique is employed to obtain solutions.